Modelling and implementation of 9tka game with MaxN algorithm - Dina Stefani; Frederikus J.; Irene Astuti Lazarusli; Samuel Lukas; Petrus Widjaja (Universitas Ahmad Dahlan, 2019)
9tka is a board game created by Adam Kaluza. The game can be played with 2 up to 4 players, with the goal of conquering as many areas in the board as possible. The aim of this research is to implement the 9tka game into a digital game that can be played on a personal computer. The implementation will include the feature to play against computer players. The rules and game’s play of 9tka is modelled, and then implemented using Java. The Artificial Intelligence (AI) of the computer player is implemented using the MaxN algorithm, which is an extension of the minimax algorithm. Several tests were done to gauge the robustness of the implemented AI. The experiments show that the AI is capable to make a move in time less than 541 milliseconds on average, across all types of players. Moreover, from eight respondents, the average amount of human wins is 2.25 out of 5 matches, across all types of players. This shows that the implemented AI on computer player has a better chance to defeat human opponents.